If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1-3m=7(m-7)
We simplify the equation to the form, which is simple to understand
1-3m=7(m-7)
Reorder the terms in parentheses
1-3m=+(+7m-49)
Remove unnecessary parentheses
+1-3m=+7m-49
We move all terms containing m to the left and all other terms to the right.
-3m-7m=-49-1
We simplify left and right side of the equation.
-10m=-50
We divide both sides of the equation by -10 to get m.
m=5
| 29+9x=101 | | -9/7-9/5w=-9/2 | | 1/2x+7=8 | | 3x+6+2=3(x+2)+2 | | 9=16+-7m | | 17x-7-5x+23=28 | | -0.5*2= | | 1/5n=-7 | | 4a+5-a=-2a | | -3(v-4)=30 | | 11/4x=22 | | 9x-3-2x=-31 | | 3n+7=14+3n | | 4a+6-a=-2a | | 15/9=8/z | | 11/3+3n=4/5n+15 | | 4+x/4=5 | | 3x+17-2x+20=-3 | | 9(3x+6)-6(7x-3)= | | 2x+9+2x+8+2x=2x+2x+3x+8 | | y=0.5x-0.2 | | 40v^2+19v-3=0 | | 4x+7y=-14 | | 4/x=8/40 | | 36-a=-36 | | a/8+7=8 | | 7a=10a/2 | | 10x+89=259 | | 1.33333x+2=0.25x+-9 | | 27=19w | | 2w+w=2(16/3) | | 6(x+1/8-2x-3/16)=3(3x/4-1/4)-3/8(3x-27) |